Laboratory measurement of displacement on shallow foundation in uniform sand using particle image velocimetry technique - Siti Noor Linda, Taib; Lau, See Hung; Prabir, Kumar Kolay (Penerbit Universiti Teknologi Malaysia, 2013)
Particle Image Velocimetry (PIV) is one of the non-intrusive techniques recently being utilized for measuring soil displacement in geotechnical engineering. The work discussed in this paper focuses on the application of an image processing tool known as MatPIV, a freeware readily available to the general users. The test programmes involved measurement and visualization of the behavior of displaced soil under various type of loadings and sizes of the foundation plate. Prior to testing, validation test was performed to study on the validity of measurements produced by MatPIV by comparing its measurements with the actual. Boundary analysis was also performed to justify on the configuration chosen for the model box used in both validation and experimental set-ups. In addition, a set of 70 displacement data was also studied in the validation test and a further statistical analysis on the data showed an acceptable accuracy of 98.8% for the MatPIV analysis when compared to the actual measured displacement. Hence, further test programmes which consisted of various soil-structure interaction conditions were performed. This comprehensive analysis showed that the diameter of loading rods and the sizes of foundation plate do affect the behavior of soil displacement under centric structural loading and was shown successfully via MatPIV